The Association between Oxidative Stress and Cardiac Functions in Infants Born to Preeclamptic Mothers - Arman, Didem; Ercin, Secil; Topcuoğlu, Sevilay; Kaya, Ayşem; Yavuz, Taner; Karatekin, Güner; Ovalı, Fahri (American Journal of Perinatology, 2019)
Objective The present study aimed to assess the global oxidant and antioxidant status in infants born to preeclamptic mothers and their correlation with cardiac functions.Study Design We compared 40 infants born to preeclamptic mothers with 40 premature infants born to normotensive mothers. We assessed the relationship between echocardiographic measurements and total antioxidant capacity (TAC) and total oxidant status (TOS) values.Results In the study group, TAC, TOS, and oxidative stress index (OSI) levels were significantly higher in the cord blood (p = 0.03, 0.04, and 0.039, respectively) than in the control group. We did not observe any correlation between echocardiographic measurements and TAC, TOS, and OSI levels in infants born to preeclamptic mothers.Conclusion Compared with the control group, despite higher TAC levels in infants born to preeclamptic mothers, concurrent elevated OSI levels reveal that the oxidant–antioxidant balance is disturbed in favor of oxidants. Furthermore, the findings of this study suggest that echocardiographic parameters are unaffected by the oxidant status.
Keywords: prematurity; preeclampsia; oxidative stress; cardiac functions